FEATURES OF MODELING COMPANY DEVELOPMENT SCENARIOS BASED ON CHANGES IN STRATEGIC MANAGEMENT - Азізов, О. (SWorldJournal, 2025)
The article explores the role of scenario planning in modern strategic management of companies, analyzes the concept of scenario planning as a flexible tool for predicting the development of events in conditions of uncertainty. The relationship between sc